Physicochemical Characteristic and Antioxidant Activity in Vitro of Seabuckthorn Fruit Polysaccharide - Zhiqiang ZHAO; Xucheng ZHU; Zhenying FENG; Haiting CHEN; Jiale YU; Di YAN; Songquan SONG; Yingbin SHEN; Cuifang TANG (Shipin gongye ke-ji, 2023)
In this study, a polysaccharide was extracted and separated from seabuckthorn fruits by water extraction. The physicochemical characteristics were characterized, including monosaccharide composition, molecular weight, microscopic characterization, thermal stability, and rheological properties. Four models were used to evaluate its antioxidant activity in vitro. The results showed that the main component of the polysaccharide was an acidic pectin polysaccharide with a molecular weight of 37.82×104 Da. It was mainly composed of fucose, rhamnose, arabinose, galactose, glucose, xylose, and glucuronic acid with a molar ratio of 0.244: 0.098: 0.265: 0.075: 0.091: 0.081: 0.103. It also contained α- and β-glycoside bonds and carbonyl, carboxyl, aldehyde and hydroxyl groups, with three spiral and lamellar structures. The polysaccharide had strong thermal stability whose solution exhibited pseudoplastic properties. Seabuckthorn berry polysaccharide had a strong antioxidant capacity in vitro and showed significant scavenging ability on DPPH free radicals. In addition, it presented chelating ability on Fe2+. In conclusion, seabuckthorn fruit polysaccharide has the potential to serve as functional food additives.